Extinction and Scattering of Light by Magnetic Colloidal Nanoparticles - C.V. Yerin (Журнал нано- та електронної фізики)
The peculiarities of scattering and extinction of light by colloids with different concentrations of magnetite nanoparticles are investigated. The light absorption effect on spectral dependencies of optical density of magnetic colloid are observed. According to dynamic light scattering experiments, particle size distributions for samples with different concentration of nanoparticles are defined.